Uniwersalne mechanizmy organizacji jako archetypy systemów sztucznej inteligencji wspomagających zarządzanie - Krupski, Rafał (Universal mechanisms of an organization as archetypes of artificial intelligence systems supporting management, 2006)
The article presents the project of production regulator as the example of the solutions of the artificial intelligence system. The presented system encloses three epistemological levels of a reality projection. Both a decision-maker man and supporting him (in a decision process) presented as the algorithm subsystems including separated phases of this process have been integrated in one system. Natural intelligence was conjugated with artificial intelligence in one system which makes decisions in a management process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 124-131